(untitled) (Journal of Foreign Language Studies, 2024)
In communication in Russian as well as in other languages, personal pronouns are used extensively and they are known as tools of communication. However, if you want to get the excitement in communicating, it is necessary to know how to use pronouns ты and вы because this is the main means to establish relationships and maintain communication process. For Vietnamese who learn Russian, using these two pronouns correctly is not easy. Besides, the translating them from Russian into Vietnamese is quite complicated. Helping students understand more about the usage and the meaning of these pronouns, article analyzed the significance and listed the translation of pronouns я, ты, вы based on the dialogues between Pavel with his comrades and the enemy in novel “How the steel was tempered” by N.Ostrovsky.